Research of the Thermal and Strength Properties for Materials Obtained with Sunflower Oil - Balo, Figen; Yucel, H. Lutfi; Ucar, Aynur (Taylor & Francis Ltd, 2011)
The use of pulverized fly ash (PFA) obtained from thermal power plants and epoxidized sunflower oil (ESFO) as recycled material in the construction industry was investigated. Epoxidized sunflower oil, clay (C) and pulverized fly ash were mixed at various proportions and were fired at 160, 180 and 200 degrees C. The thermal conductivity and strength (compressive strength, tensile strength and abrasion loss) of the samples were determinated. The lowest value of thermal conductivity, 0.25 W/mK, was measured for the sample with a 70% FA/30% C ratio and 50% ESFO processed at 200. C. This sample had the lowest compressive-tensile strength (3.28 MPa-0.633 MPa) and the highest abrasion loss (4.39%). The highest compressive-tensile strengths and the lowest value of abrasion loss observed, were 7.21 MPa-0.939 MPa and 1.15%, respectively. (C) Koninklijke Brill NV, Leiden, 2011
Keywords: Thermal conductivity; mechanical properties; pulverized fly ash; epoxidized sunflower oil; clay